ADAPTING INSTRUCTION TO STUDENT DIFFERENCES IN AN INDIVIDUALIZED SCIENCE PROGRAM. - Sheehan, Daniel S.; Hambleton, Ronald K. (Journal of Research in Science Teaching, 1977)
The article investigates the types of instructional models that maximize outcome measures for a variety of student characteristics. The four types of instructional models designed for ninth-grade science course includes the teacher-directed treatment, the media treatment, the reading treatment and the programmed instruction treatment. The result of the study provide guidelines to science teachers on how to assign students to the treatment groups on the basis of Test Anxiety Scale for Children scores. It indicates that control was lacking in the execution of the instructional treatments.